2006
DOI: 10.1029/2005tc001894
|View full text |Cite
|
Sign up to set email alerts
|

Development of the southern Eastern Cordillera, NW Argentina, constrained by apatite fission track thermochronology: From early Cretaceous extension to middle Miocene shortening

Abstract: For the Puna Plateau and Eastern Cordillera of NW Argentina, the temporal and spatial pattern of deformation and surface uplift remain poorly constrained. Analysis of completely and partially reset apatite fission track samples collected from vertical profiles along an ESE trending transect extending from the plateau interior across the southern Eastern Cordillera at ∼25°S reveals important constraints on the deformation and exhumation history of this part of the Andes. The data constrain the Neogene Andean de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
161
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(176 citation statements)
references
References 61 publications
13
161
0
2
Order By: Relevance
“…The Middle Eocene deformation-sedimentation age ascribed here to the Quebrada de los Colorados Formation is comparable to other deformational ages defined for distinct areas of northwestern Argentina (Puna and Cordillera Oriental), including the Altiplano and Cordillera Oriental of southeastern Bolivia (Horton, 2005;Ege et al, 2007) and the Atacama region of Chile (Arriagada et al, 2006). Recent thermo-chronology (AFT) studies of granite from eastern Puna and Cordillera Oriental (Haschke et al, 2005) have suggested a contractional episode during the Late Eocene-Early Oligocene (Coutand et al, 2001;Coutand et al, 2006;Deeken et al, 2006). On the other hand, Hongn et al (2007) documented a Middle Eocene deformation in the northern Calchaquí Valley (Fig.…”
Section: Correlation and Regional Implicationsmentioning
confidence: 81%
See 2 more Smart Citations
“…The Middle Eocene deformation-sedimentation age ascribed here to the Quebrada de los Colorados Formation is comparable to other deformational ages defined for distinct areas of northwestern Argentina (Puna and Cordillera Oriental), including the Altiplano and Cordillera Oriental of southeastern Bolivia (Horton, 2005;Ege et al, 2007) and the Atacama region of Chile (Arriagada et al, 2006). Recent thermo-chronology (AFT) studies of granite from eastern Puna and Cordillera Oriental (Haschke et al, 2005) have suggested a contractional episode during the Late Eocene-Early Oligocene (Coutand et al, 2001;Coutand et al, 2006;Deeken et al, 2006). On the other hand, Hongn et al (2007) documented a Middle Eocene deformation in the northern Calchaquí Valley (Fig.…”
Section: Correlation and Regional Implicationsmentioning
confidence: 81%
“…This area recorded tectonic overprints from the Upper Neoproterozoic-Lower Paleozoic deformation affecting the basement, a widespread phenomenon in NW Argentina (Turner and Mon, 1979;Mon and Salfity, 1995) that has lasted to the present. Older structures were reactivated during subsequent deformation, especially during the Cretaceous rifting and Cenozoic Andean-shortening (Hongn and Seggiaro, 2001;Riller and Hongn, 2003;Carrera et al, 2006;Deeken et al, 2006).…”
Section: Geological Settingmentioning
confidence: 96%
See 1 more Smart Citation
“…1). The Eastern Cordillera has been the site of deformation and exhumation since at least the Miocene (Coutand et al, 2001Deeken et al, 2006;Carrapa et al, 2011a). Eastward propagation of the deformation through the region in the late Cenozoic was responsible for disruption of the regional foreland basin system.…”
Section: Introductionmentioning
confidence: 99%
“…Contraction would facilitate squeezing out low density melt from the mush zone, which would in turn ascend to a level of neutral buoyancy higher in the crust. This uplift, which began at 6-5 Ma, occurred in an out-of-sequence order on steep east-and west-dipping reverse faults (see Deeken et al 2006). The early uplift could be linked with different phases of the Toconquis eruptions, and the younger faults further to the east to the Galán extracaldera and intracaldera ignimbrites.…”
Section: Crustal Evolution Of the Cerro Galán Ignimbritesmentioning
confidence: 99%